Correction: Kidney damage on fertility and pregnancy: A Mendelian randomization. - Jin Ren; Qiuyan Huang; Xiaowei Nie; Xingli Tong; Qi Yao; Ge Zhou (PLoS ONE)
[This corrects the article DOI: 10.1371/journal.pone.0288788.].